PERFORMANSI UJUB: DOA DAN KOMUNIKASI TIGA ALAM DALAM TRADISI BERSIH DESA KRISIK DI BLITAR PROVINSI JAWA TIMUR - Fitrahayunitisna Fitrahayunitisna (Balai Penelitian dan Pengembangan Agama Semarang, 2018)
Slametan Bersih Desa is a Javanese folklore in Krisik village. Ujub as oral literature is the richness of Indonesian culture. In facing challenges of the modern era, speakers of ujub are less from the young generation. Most of them are from the old generation. This research is qualitative research with structural and ethnographic approaches. The focuses of the problem are (1) the performance of orality ujub in the tradition of Bersih Desa, (2) the object and the theme of prayer in ujub Bersih desa, and (3) the communication of the three worlds in ujub Bersih desa. This research aims to describe the performance of ujub orality, objects, and themes of prayer, and communication of the three worlds which become the function of ujub orality in order to increase documentation and interpretation of the richness of oral literature as Indonesian folklore. By knowing the performance and the formulas of the ujub orality, it is easier for the younger generation of speakers to formulate the memory of ujub orality. The research shows that performance of ujub presented at the main ritual of slametan has a pattern of matra free text, has a rhyme of asonasi, desonasi, and alliteration, the rhythm of efony, and contains the formulaic pattern and formulaic expressions. The content of the prayer in ujub got influences from Islam and it has syncretism between the religion of Islam and the traditions of Java. The text of ujub has a function to communicate the three worlds which are between the humans’ world, the spirits world, and the God world.